1975
DOI: 10.1210/jcem-41-1-27
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Decreased Serum Triiodothyronine Concentration in Patients with Nonthyroidal Disease

Abstract: Serum thyroxine (T4) and triiodothyronine (T3) concentration and binding were measured in 34 clinically euthyroid patients hospitalized for a wide variety of nonthyroidal diseases. Despite clinical euthyroidism, serum T3 was in the hypothyroid range (less than 90 ng/100 ml) in 24 of the 34 patients, and the mean serum T3 of this group, 78.4 +/- 38.3 (SD), was significantly decreased from that of control, 134.0 +/- 29.3 ng/200 ml. Mean serum T4 levels were essentially the same in both groups, 7.3 +/- 2.0 for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
101
3
4

Year Published

1979
1979
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(122 citation statements)
references
References 0 publications
14
101
3
4
Order By: Relevance
“…In the present study, free T4 values were not changed with age between 40-69 years in agreement with similar data examining the FT4 index (Bernudez et al 1975 ;Gregerman and Davis 1978). Meanwhile, Malvaux et al (1966) reported that FT4 was decreased in adolescents as compared to adults.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, free T4 values were not changed with age between 40-69 years in agreement with similar data examining the FT4 index (Bernudez et al 1975 ;Gregerman and Davis 1978). Meanwhile, Malvaux et al (1966) reported that FT4 was decreased in adolescents as compared to adults.…”
Section: Discussionsupporting
confidence: 93%
“…The noncalorigenic product of T4 monodeiodination 3,3'-5'-triiodothyronine (reverse T3, rT3), is generated from inner ring deiodination. A decrease in the serum concentration of T3 (6)(7)(8)(9)(10) and the production of T3 from T4 (11)(12)(13) have been demonstrated in man under a variety of circumstances. An increase in serum rT3 concentration almost always occurs in these states (9,10,14,15), probably due to a decrease in rT3 clearance rather than enhanced rT3 production (11,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…These include fasting or partial caloric deprivation (8)(9)(10)(11)(12); diabetes (13)(14)(15); surgical stress (16,17); moderate or severe chronic illness (18)(19)(20); cirrhosis (21,22); and a number of drugs, including Abbreviationis used in this paper: I-, iodide; T3, 3,5,3'-triiodothyronine; T4, thyroxine; T3-neogenesis, generation of T3 from T4.…”
mentioning
confidence: 99%